Antibacterial Activity and Cytotoxicity Screening of Acyldepsipeptide-1 Analogues Conjugated to Silver/Indium/Sulphide Quantum Dots - Sinazo Z. Z. Cobongela; Maya M. Makatini; Bambesiwe May; Zikhona Njengele-Tetyana; Mokae F. Bambo; Nicole R. S. Sibuyi (MDPI AG, 2024)
The continuous rise in bacterial infections and antibiotic resistance is the driving force behind the search for new antibacterial agents with novel modes of action. Antimicrobial peptides (AMPs) have recently gained attention as promising antibiotic agents with the potential to treat drug-resistant infections. Several AMPs have shown a lower propensity towards developing resistance compared to conventional antibiotics. However, these peptides, especially acyldepsipeptides (ADEPs) present with unfavorable pharmacokinetic properties, such as high toxicity and low bioavailability. Different ways to improve these peptides to be drug-like molecules have been explored, and these include using biocompatible nano-carriers. ADEP1 analogues (SC005-8) conjugated to gelatin-capped Silver/Indium/Sulfide (AgInS2) quantum dots (QDs) improved the antibacterial activity against Gram-negative (Escherichia coli and Pseudomonas aeruginosa), and Gram-positive (Bacillus subtilis, Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus) bacteria. The ADEP1 analogues exhibited minimum inhibition concentrations (MIC) between 63 and 500 µM, and minimum bactericidal concentrations (MBC) values between 125 and 750 µM. The AgInS2-ADEP1 analogue conjugates showed enhanced antibacterial activity as evident from the MIC and MBC values, i.e., 1.6-25 µM and 6.3-100 µM, respectively. The AgInS2-ADEP1 analogue conjugates were non-toxic against HEK-293 cells at concentrations that showed antibacterial activity. The findings reported herein could be helpful in the development of antibacterial treatment strategies.